Acervo censurado: radiodocumentário sobre as músicas vetadas na ditadura civil-militar no Brasil (1964-1985) que fazem parte do acervo de vinis da Rádio Universidade de Santa Maria - Miranda, Rejane da Silva (2024)
This master's dissertation is linked to the Research Line of History and Cultural Heritage, of the Postgraduate Program in Cultural Heritage (PPGPC), with a professionalizing focus, in Universidade Federal de Santa Maria (UFSM). The research aimed to investigate, in the collection of vinyl discs of Radio Universidade de Santa Maria, Public Broadcaster of the UFSM, the artists, discs and songs that were censored during the Civil-Military Dictatorship in Brazil (1964-1985). Based on the analysis of this information, a radio documentary was produced divided into 5 episodes, presenting the main works and artists subjected to censorship. The collection, which houses 6.654 vinyl discs, has been preserved, identified and cataloged by the UFSM, thus constituting a cultural heritage of the institution. In view of this, the LPs were treated as documents, as from them it was possible to extract fundamental information for the development of the dissertation, such as year of release, record label, composers and censored songs. Thus, from documentary research, it was possible to report the history of broadcasting and the consequences of censorship in the programming of the broadcasters; to understand how the functioning of the Division of Censorship of Public Entertainment, the body responsible for authorizing and censoring the literary-musical pieces, and how the closure and silencing of artists had an impact on the cultural production of that period. The radio documentary will be broadcast in the programming of the UFSM, AM and FM Radios, and will be available on Eduplay, the largest video portal for higher education in Brazil.